(untitled) (Nigerian Journal of Technology, 2018)
With the huge quantum of energy that is often wasted from the diesel engine exhaust of a typical fishing vessel, this research was conducted. It focuses on the potential of harnessing the exhaust heat from the engine in vapour absorption refrigeration system (VARS) of the vessel. The VARS considered here employs ammonia as refrigerant with water as the absorbent which are environmentally-friendly. The system was considered integral to a diesel engine which provides the heat energy needed. The system was analyzed theoretically by calculating the performance using thermodynamics analysis developed and applied to the various components of the VARS. The results show that with 349.69 kW heat energy from the exhaust gas, 314.50 kW accounting for about 90 % was utilized to vapourize the ammonia from its solution. Also, with a generator temperature of 1300C the coefficient of performance (COP) was obtained as 29.67 % which is low when compared to the COPs of vapour compression refrigeration system (VCRS). However, the work shows that the twin benefits of environmental pollution reduction as well as waste energy utilization were achieved. http://dx.doi.org/10.4314/njt.v37i4.11